2017
DOI: 10.26803/ijlter.16.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Responding to the Unique Needs and Challenges Facing Adjunct Faculty: A Longitudinal Study

Abstract: Abstract. This study reports the results of a longitudinal study of adjunct faculty at a large research-intensive institution. A needs assessment found that adjunct faculty felt isolated and disconnected from their departments and colleagues, and reported a lack of formal and informal supports needed for success in their instructional roles. These findings guided the development and campus-wide implementation of adjunct-specific programming and resources. A program evaluation found improvements in adjunct facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…Third, SF could benefit from being able to access knowledge and skills relevant to their teaching through convenient FD, possibly progressing them towards becoming a medical educator . Finally, SF who rate their connectedness with the teacher community lower may be supported by developing (or including them in) FD communities that increase their connectedness to the respective department . We suggest that implementing these changes may move SF on the continuum towards a more developed model of a medical educator, which may benefit students.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Third, SF could benefit from being able to access knowledge and skills relevant to their teaching through convenient FD, possibly progressing them towards becoming a medical educator . Finally, SF who rate their connectedness with the teacher community lower may be supported by developing (or including them in) FD communities that increase their connectedness to the respective department . We suggest that implementing these changes may move SF on the continuum towards a more developed model of a medical educator, which may benefit students.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, SF who realise they want to or need to develop as medical educators may turn to their teaching community within the respective department to validate their identity, as suggested in the SF model. However, their limited experience of connectedness to and appreciation from that teaching community as an SF (‘I do not belong’, ‘I have limited contact with faculty’, ‘there is a lack of institutional engagement’, ‘I am excluded’, ‘I am invisible’, and ‘I am an outsider’) has the potential to hinder their identity as teachers. We feel that both these explanations (identity from their clinician role and lack of appreciation and a teaching community) may have some value in explaining the limited value of connectedness and appreciation in predicting identity as a medical educator in our SF model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjuncts were more likely than full-timers to report feelings of isolation, marginalization, and disconnectedness (Buch et al, 2017;Buch & McCullough, 2016;Levin & Hernandez, 2014). Some studies found that adjuncts often reported a lack of institutional support for their work and feelings of disconnection from departments and colleagues, which diminished collegiality and a sense of community (Buch et al, 2017;Kezar & Maxey, 2016b;Kimmel & Fairchild, 2017;Ott & Cisneros, 2015).…”
Section: Institutional Connectedness and Job Satisfactionmentioning
confidence: 99%